2019
DOI: 10.3390/jcm8111852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Concomitant Orbital Floor Fractures in Patients with Head Trauma Using Conventional Head CT Scan: A Retrospective Study at a Level II Trauma Center

Abstract: Background: Patients with head trauma may have concomitant orbital floor fractures (OFFs). The objective of our study was to determine the specific CT findings and investigate the diagnostic performance of head CT in detecting OFFs. Methods: We analyzed 3534 head trauma patients undergoing simultaneous head and facial CT over a 3-year period. The clinical data and specific head CT findings between patients with and without OFFs were compared. Results: In our cohort, 198 patients (5.6%) had OFFs visible on CT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In patients with facial fractures, X-ray and CT was identified as low-value in five studies [ 278 282 ], as imaging did not change the management of the patient. One study introduced the use of ultrasound combined with an X-ray, instead of CT in zygomatic arch and mandibular fractures [ 281 ].…”
Section: Resultsmentioning
confidence: 99%
“…In patients with facial fractures, X-ray and CT was identified as low-value in five studies [ 278 282 ], as imaging did not change the management of the patient. One study introduced the use of ultrasound combined with an X-ray, instead of CT in zygomatic arch and mandibular fractures [ 281 ].…”
Section: Resultsmentioning
confidence: 99%
“…10 Third, the absence of hemosinus on head computed tomography may be considered an indicator to exclude the presence of paranasal sinus wall fracture, 19,28 and some previous studies have also demonstrated a potential role of existing maxillary hemosinus in the prediction of midfacial fracture. 9,29 However, the maxillary sinus may not be included in the scanning range of routine head computed tomography; therefore, this variable was excluded during the model development to facilitate the general application of our risk-prediction model. Fourth, although the prediction model consisting of an increased number of variables might achieve high diagnostic performance, the related complexity could potentially limit its accessibility for clinical implementation in the trauma setting.…”
Section: Discussionmentioning
confidence: 99%